A Study To Evaluate The Effectiveness Of Cognitive Exercises In Improving Cognitive Abilities Of Elderly With Dementia In Selected Old Age Home, Namakkal - Nirosha, V.; Raghavendran, M.; Anitha, J.; Jayanthi, P.; Jovanna, V.; Gayathri, V. (Journal of Neonatal Surgery, 2025)
A normal aspect of ageing is the potential for cognitive ability to deteriorate somewhat as people get older. On the other, minor cognitive impairment or even dementia or a significant neurocognitive illness may develop if this cognitive decline worsens. A common problem among people over 60 is cognitive deterioration. It is anticipated that India’s old population would triple to two billion people. The aim of this study is to evaluate the effectiveness of cognitive exercises in improving cognitive functions & to find out the association between post-test level of cognitive functions with their selected Demographic variables among the elderly with dementia in a selected old age home in Namakkal. A quasi-experimental pretest and post-test design was adopted for this study. A total of 40 elderly with dementia were selected using purposive sampling technique from a selected old-age home, Namakkal & those who fulfilled the inclusion criteria. Cognitive functions were assessed using a standardized tool Mini-Mental Status Examination (MMSE). Cognitive exercises, including memory tasks, puzzles & attention-based activities were administered. The data were analyzed using descriptive & inferential statistics. The average score for cognitive functions in older adults with dementia was 21.65 with 34.36% prior to the intervention, & it is 18.22 with 28.92% mean percentage after the intervention. Elderly with dementia had pretest median & SD scores of 21 & 4.67 for cognitive functions, and post-test median and SD scores of 18 & 4.02. For cognitive function, the t-test value is 7.07. At the 0.05 level of significance, the computed value of 7.07 is greater than the tabulated value of 1.96 at 39 df. It indicates that cognitive exercises are useful in enhancing the cognitive functions among elderly with dementia. The chi-square analysis was used to find the association between the post test level of cognitive functions among elderly with their selected demographic variables. It shows that the calculated value is greater than the table value in occupation before entering the old-age home and length of stay are significantly associated with their selected demographic variables.